ARISTOTELIAN ETHICS IN EFL PEDAGOGY: INTEGRATING BUGIS PHILOPHICAL VALUES IN ENGLISH LANGUAGE YEACHING IN PINRANG, SOUTH SULAWESI - Nurul Hikmah; ST Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the integration of Aristotelian ethics and Bugis philosophical values in the pedagogy of English as a Foreign Language (EFL) in the local context of Pinrang, South Sulawesi. The main problem of this study lies in the limited EFL learning model that systematically accommodates local ethical and cultural dimensions, so that learning tends to be technical-linguistic oriented and does not touch the formation of students' character. This research aims to construct an EFL pedagogical framework based on virtue ethics and Bugis local wisdom as an alternative to a more humanistic and contextual learning paradigm. The methodology used is a qualitative approach with the method of philosophical inquiry through conceptual analysis and literature studies of relevant classical and contemporary works. The findings of the study show that the concepts of phronesis, arete, and eudaimonia in Aristotelian ethics have a conceptual correspondence with the values of siri', sipakatau, and sipakalebbi in the Bugis tradition. The integration of the two frameworks results in a conceptual model of EFL pedagogy that is oriented towards the development of communicative competencies as well as character building. This study concludes that a philosophical approach based on local values has the potential to enrich the philosophy and paradigm of EFL in the context of language education in Indonesia.